Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

Islamic Radicalization in Northern Mozambique: The Case of Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Cadernos IESE)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui. ----- This research report is a first attempt to address the phenomenon in order to understand the complexity of the dynamics not only in the origin of the Al-Shabaab group but also in the structure of the conflict and violence in Cabo Delgado. Almost two years after the first attack on Mocímboa da Praia (5 October 2017), the phenomenon has been the subject of multiple interpretations, from the (at least public) Mozambican government’s preferred thesis of a conspiracy driven by external forces opposed to Mozambique’s development, through the land conflict against the backdrop of the area’s natural resources thesis, to the sect (Morier-Genoud, 2019) and jihadism theses, in the context of the growing dynamics of violent extremism in the countries of the region i.e. Tanzania, Kenya and the Great Lakes region. While highlighting this last thesis (jihadism), our exploratory research has shown that the phenomenon is complex and requires profound multidisciplinary research that takes into account a multiplicity of historical, social, political, economic and religious factors. This is why, rather than draw conclusions, this report ends with a series of questions: • Why is Mocímboa da Praia the epicentre of the phenomenon? • How does the Mozambican state deal with the proliferation of religious institutions in the country? • What are the implications of the Islamic radicalization phenomenon for investments in the country’s northern region? To what extent can these investments heighten or reduce local cleavages and contribute to Islamic radicalization phenomenon? • To what extent does the Islamic radicalization phenomenon affect current efforts to stabilize the country politically and economically? • To what extent can regional dynamics (Tanzania, Kenya, Great Lakes region) influence the evolution of the phenomenon in Mozambique? • What kind of policies (including security) does the country need to address the phenomenon? • What lessons does the phenomenon bring to the state-building process in Mozambique? These questions feed into the ongoing research program at the Institute for Social and Economic Studies (IESE) since early 2019, involving researchers from IESE and other research centres, entitled “State, Violence and Development Challenges in Cabo Delgado”.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude